Strategi Dinkominfo Kota Surabaya Dalam Meningkatkan Digital Literacy Untuk Mendukung Smart City [Strategy of Surabaya City Communication and Information Department in Improving Digital Literacy to Support Smart City] - Moch. Andre Firmansyah; Kalvin Edo Wahyudi (Spirit Publik: Jurnal Administrasi Publik, 2024)
Digital literacy is an important element for the people of Surabaya City in facing the digital era like today. Digital literacy can provide easier access to information. With the ability to access and evaluate information online, people can get news, research or other resources more quickly. Digital literacy can also help people recognize potential security risks such as online fraud and hoax news. Therefore, efforts to increase digital literacy in the people of Surabaya City are very important so that they can take full advantage of the digital era and can overcome the challenges that arise wisely. This research aims to describe the strategy of the Surabaya City Communication and Informatics Service (Dinkominfo) in improving digital literacy community to support smart city. The research method adopted is descriptive qualitative using data collection techniques through observation, interviews, and documentation. The theory on which this research is based is the SOAR (Strengths, Opportunities, Aspirations, Results) analysis model. The results of the research show that the strategies applied in improving community digital literacy to support the smart city concept in Surabaya City, among others 1) Strengths, namely the Communication and Informatics Department has a program Broadband Learning Center (BLC), has many relationships in making the digital literacy program a success, has supporting facilities and infrastructure. 2) Opportunities are carried out by utilizing social media as a forum for educating the public regarding digital literacy, collaborating with stakeholders such as collaborating with educational institutions and related agencies. 3) Aspirations responded by providing supporting facilities for digital literacy improvement programs such as computers and instructors, completing facilities and conducting evaluations. 4) The perceived results are that people can understand the pillars of digital literacy, supporting facilities and infrastructure so that people become comfortable in learning about information and communication technology